Análisis del desinterés en la lectura en los estudiantes de Educación General Básica Superior de la Unidad Educativa “Nuestra Señora de Fátima”. - Rodríguez, Kethy M. (2022)
The main objective of this article was the analysis of the incidences of disinterest in reading in the three courses of Higher General Basic Education at the Nuestra Señora de Fátima Educational Unit, through the determination of factors of influence that surround them such as in the classroom and at home. For the development of the research a mixed qualitative-quantitative approach was used, with an exploratory-descriptive design, with a field research type and as techniques for data collection a survey directed to 70 students of Basic Education of the institution and an interview to 3 teachers of the subject of Language and Literature were used. Among the results obtained the following stand out: lack of motivation in the family and educational context, lack of a reading area with material of interest, absence of reading culture at home, either due to their low educational and economic level. Given the conditions in the academic context, it is revealed that they show interest in reading, but because they have to fulfill an obligation or task, they do not enjoy this activity and tend to show low academic performance, difficulty in reading comprehension, decoding problems, spelling mistakes and lack of criticality. Similarly, it is determined that teachers implement reading techniques such as workshops, class discussions, representations, which limit students, so other strategies that seek to improve the reading habit to strengthen cognitive processes should be used.